2009
DOI: 10.1111/j.1460-9568.2009.06629.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid cortical reorganisation and improved sensitivity of the hand following cutaneous anaesthesia of the forearm

Abstract: The cortical representation of various body parts constantly changes based on the pattern of afferent nerve impulses. As peripheral nerve injury results in a cortical and subcortical reorganisation this has been suggested as one explanation for the poor clinical outcome seen after peripheral nerve repair in humans. Cutaneous anaesthesia of the forearm in healthy subjects and in patients with nerve injuries results in rapid improvement of hand sensitivity. The mechanism behind the improvement is probably based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
56
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 38 publications
7
56
0
Order By: Relevance
“…These improvements were accompanied by a shift of the cortical representations of the ulnar skin area of the hand and lip into the deafferented representations of parts of the hand, and a significant decrease of intracortical inhibition within the muscle representation of the extensor digiti minimi muscle . Similarly, Björkman et al (2009) reported increased right hand sensitivity and an expansion of its representation within SI in healthy subjects during TFD of the right forearm by a local anesthetic cream.…”
Section: Introductionmentioning
confidence: 77%
“…These improvements were accompanied by a shift of the cortical representations of the ulnar skin area of the hand and lip into the deafferented representations of parts of the hand, and a significant decrease of intracortical inhibition within the muscle representation of the extensor digiti minimi muscle . Similarly, Björkman et al (2009) reported increased right hand sensitivity and an expansion of its representation within SI in healthy subjects during TFD of the right forearm by a local anesthetic cream.…”
Section: Introductionmentioning
confidence: 77%
“…Calford and Tweedale (1988) described rapid SI changes (within a single day) following single digit amputation in flying foxes, and in humans, cortical reorganization can occur within hours following brief limb or digit anesthesia (Rossini et al, 1994;Björkman et al, 2009). This relatively rapid reorganization likely results from disinhibition or facilitation of existing subthreshold inputs onto neighboring cortical representations.…”
Section: Latent Lateral Synapsesmentioning
confidence: 99%
“…Despite the well established phenomenon of cortical reorganization, it remains unknown whether in humans, this functional reorganization results from physical changes in brain anatomy, such as dendritic sprouting, or simply reflects an unmasking of already existing dormant synapses. Although it has recently been reported in humans that SI reorganization can occur within hours of limb anesthesia, supporting the existence of dormant synapses (Björkman et al, 2009), it remains unknown whether such an "unmasking" is responsible for the large SI reorganization that occurs following limb amputation or spinal cord injury (SCI).…”
Section: Introductionmentioning
confidence: 99%
“…Physical insults to the skin may fail to elicit nociceptive withdrawal reflexes when sensory nerves originating from the skin area have been injured. Reorganization of cortical somatotopic maps (Calford and Tweedale, 1988;Björkman et al, 2009) and potentiation of cortical responses in response to stimulation of nearby nerves (Tinazzi et al, 1997) are quickly induced within a few hours after nerve injury, possibly for facilitating nociceptive withdrawal reflexes. Our results suggest that the lowfrequency basal firing in touch-sensitive nerves has a role to inform the absence of disconnection in peripheral sensory nerves to the spinal cord.…”
Section: Basal Firing In Sensory Nervesmentioning
confidence: 99%
“…However, the relationship between these two phenomena has not been well investigated thus far, because the underlying mechanisms are considered to be different. Neuropathic pain is established as a consequence of a complex cascade of inflammation and gene expression (Campbell and Meyer, 2006), whereas cortical plasticity is found within a few hours after peripheral nerve cutting (Calford and Tweedale, 1988;Björkman et al, 2009). The complexity of the mechanisms involved in neuropathic pain prevents us from identifying the primary etiology and developing an effective therapy for neuropathic pain.…”
Section: Introductionmentioning
confidence: 99%